Auswirkungen des flächendeckenden Einsatzes von Mobile Stroke Units: das ProHTA-Simulationskonzept - Kriza, Christine; Djanatliev, Anatoli; Meier, Florian; Wahlster, Philip; Gantner-Bär, Marion; Hofmann, Bernd; German, Reinhard; Sedlmayr, Martin; Kolominsky-Rabas, Peter (Tagungsband der 7. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.auswir

Conceptual Modeling for Prospective Health Technology Assessment - Gantner-Bär, Marion; Djanatliev, Anatoli; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Studies in health technology and informatics, 2012)
Prospective Health Technology Assessment (ProHTA) is a new and innovative approach to analyze and assess new technologies, methods and procedures in health care. Simulation processes are used to model innovations before the cost-intensive design and development phase. Thus effects on patient care, the health care system as well as health economics aspects can be estimated. To generate simulation models a valid information base is necessary and therefore conceptual modeling is most suitable. Project-specifically improved methods and characteristics of simulation modeling are combined in the ProHTA Conceptual Modeling Process and initially implemented for acute ischemic stroke treatment in Germany. Additionally the project aims at simulation of other diseases and health care systems as well. ProHTA is an interdisciplinary research project within the Cluster of Excellence for Medical Technology - Medical Valley European Metropolitan Region Nuremberg (EMN), which is funded by the German Federal Ministry of Education and Research (BMBF), project grant No. 01EX1013B. © 2012 European Federation for Medical Informatics and IOS Press. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.tech.IMMD.IMMD7.concep
Keywords: Conceptual model; Conceptual modeling; Health care; Health economics; Ischemic stroke treatment; Prospective health technology assessment; Simulation

Early technology foresight for medical product development through simulation: Prospective Health Technology Assessment (ProHTA) - Kriza, Christine; Wahlster, Philip; Djanatliev, Anatoli; German, Reinhard; Gantner-Bär, Marion; Hofmann, Bernd; Reinhardt, Erich; Sedlmayr, Martin; Kolominsky-Rabas, Peter (Proceedings of the HTAi 10th Annual Meeting, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD7.earlyt

Gesundheitsökonomische Evaluierung eines hypothetischen Biomarkers in einem Prostata-Screening-Szenario in Deutschland unter Anwendung eines hybriden Simulationsmodells - Meier, Florian; Niederländer, Charlotte; Djanatliev, Anatoli; Gantner-Bär, Marion; Sedlmayr, Martin; Höllthaler, Josef; Voigt, Wieland; Schöffski, Oliver; Kolominsky-Rabas, Peter; German, Reinhard; Emmert, Martin (Tagungsband der 6. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.gesund

Health Economic Evaluation of a Contemplementary Biomarker for Hypothetical Prostate Cancer Screening in Germany - Meier, Florian; Niederländer, Charlotte; Djanatliev, Anatoli; Gantner-Bär, Marion; Höllthaler, Josef; Voigt, Wieland; Schöffski, Oliver; Kolominsky-Rabas, Peter; Emmert, Martin (Value in Health, 2013)
Prostate cancer (PCA) is the most common cancer in men worldwide. However, there is disagreement about the benefits of existing screening programs. This is mainly due to low specificity of currently utilized biomarkers. This can lead to both inappropriate medical treatment and increasing costs of care. For the future, many biotechnological developments are promising, but not all will be affordable for routine screening. The question is how much a complementary biomarker to prostate-specific antigen (PSA)-test may cost which would be applied to avoid false-positive result
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD7.health

Prospective Assessment of an innovative test for prostate cancer screening using the VITA process model framework - Gantner-Bär, Marion; Meier, Florian; Kolominsky-Rabas, Peter; Djanatliev, Anatoli; Metzger, Armin; Voigt, Wieland; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Studies in health technology and informatics, 2014)
Healthcare innovations are crucial for enhancing patient treatment and a high-quality healthcare system. However, bringing new technologies, methods and procedures into the healthcare market is challenging. Enormous amounts of financial, personnel and organizational resources are required with no upfront certainty for the medical and economic benefit. A new and innovative approach uses interdisciplinary medical, technical and economic expertise to forecast effects of healthcare innovations already at the early research and concept phase of an idea and before major investments are made. A process model framework was developed to operationalize this structured assessment of healthcare innovations. The Visionary Iterative Tailored Approach (VITA) is based on conceptual modeling, simulation and health economics evaluation. Its application for the prospective assessment of an innovative prostate cancer screening is presented.<br
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD7.prospe

Technology foresight for medical device development through hybrid simulation: The ProHTA Project - Kolominsky-Rabas, Peter; Djanatliev, Anatoli; Wahlster, Philip; Gantner-Bär, Marion; Hofmann, Bernd; German, Reinhard; Sedlmayr, Martin; Reinhardt, Erich; Schüttler, Jürgen; Kriza, Christine (Technological Forecasting and Social Change, 2015)
"Prospective Health Technology Assessment" (ProHTA) aims to develop a platform targeting health care manufacturers and decision makers that facilitates the assessment of innovative health technologies prior to their launch. The simulation has been run for the first case study of Mobile Stroke Units (MSUs). In the highly time sensitive setting of acute stroke, MSUs are an innovative approach as they aim to reduce 'time-to-thrombolysis'. The ProHTA approach focuses on interdisciplinary work related to forecasting with hybrid simulation consisting of system dynamics models for macro-simulation and agent-based models for micro-simulation. Results of the simulation show that MSUs save up to 49 min of time between ambulance call and therapy decision. Whereas without MSUs, only 0.2% of patients fall in the group with the most favourable time interval between 0 and 90 min, up to 16.6% of patients treated in MSUs fall into this group of early onset times to thrombolysis. As a flexible and primarily quantitative decision-making tool for foresight, ProHTA adds value to existing methodologies for pre-assessing health technology at a very early stage of technology research and development. With its emphasis on strategic planning, ProHTA helps to improve the efficiency of health care delivery in different settings using hybrid simulation techniques. © 2013 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD7.techno
Keywords: Early technology assessment; Foresight; Health care; Medical device; Simulation; Stroke